WARMON MORNING MARKET THE EFFECT OF EXISTENCE FOR THE DEVELOPMENT OF THE NEW CITY OF AIMAS, SORONG DISTRICT - Nany Budi Hardjayanti (LPPM Politeknik Saint Paul Sorong, 2020)
The traditional market in Indonesia is the place where economic activities begin in an area. Although now the traditional markets have been widely eroded and eliminated by the modern market, for some communities the conventional market is not only a place to buy and sell but also as a miniature of their lives which are interconnected and closely related to market activities. Warmon morning market in Malawele Aimas village is one of the examples. This market has been running for a long time. At first, there were only a few traders with the lack of place available. However, these days the Warmon morning market has developed rapidly and become one of the economic milestones in Aimas district as a capital city of Sorong Regency West Papua. The purpose of the analysis in this paper is 1] the development of the Warmon morning market in terms of the number of sellers, the velocity of money and the revenue generated from market retribution. 2] Warmon morning market contribution to Local Revenue. The collection techniques used are observation, questionnaire and interview. The result is that the Warmon morning market contributed to improving the economy of the Aimas community, not only the traders but also the surrounding community. Because with the presence of Warmon morning market, there are job opportunities for the society. Thus this has a positive impact on the progress and development of the new city of Aimas, Sorong Regency